Remission with Cabergoline in Adolescent Boys with Cushing's Disease - (:unkn) unknown (GALENOS YAYINCILIK, 2013)
Cabergoline is a long-acting dopamine receptor agonist used for treatment of patients with uncured Cushing's disease (CD) and, as a first-line treatment, was used in only limited numbers of patients. This report presents two adolescent boys with CD who were treated with cabergoline. Two adolescent boys with clinical and laboratory findings of CD are presented. No pituitary adenoma was detected by radiological investigation in either patient. Adrenocorticotropic hormone (ACTH) hypersecretion and lateralization was found by inferior petrosal sinus sampling in both patients. The initial cabergoline dose was 1mg/week and was adjusted up to 1.5 mg/week in the second patient, based on his urinary free cortisol (UFC) level. The patients responded to cabergoline treatment with normal UFC levels on the 4th and 6th months of treatment. The boys reached complete remission at the end of the 17th and 24th months, respectively. Cabergoline is effective in the control of cortisol secretion and can be considered as a first-line treatment in cases of CD.
Keywords: Cushing's disease; cabergoline; adolescent; inferior petrosal sinus sampling; EXPRESSION